2023
DOI: 10.1039/d2ta08237c
|View full text |Cite
|
Sign up to set email alerts
|

Jute stick derived self-regenerating sustainable solar evaporators with different salt mitigation mechanisms for highly efficient solar desalination

Abstract: The accumulation of salt crystals on the solar-absorbing surface of the evaporator is one of the main challenges associated with solar desalination. To solve this problem, sustainable evaporators with diverse...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…As a wide range of refractory organic contaminants was present in the actual water environment, the catalytic efficiency of the CNG-800/MF evaporator was investigated by examining organic pollutants (Figures b, S13). The CNG-800/MF evaporator completely removed SMX within 40 min and RhB and MB within 60 min, and demonstrated removal efficiencies of 90.3% for TC, 95.3% for CBZ, and 83.1% for ATZ within 60 min. These results confirmed that the as-designed CNG-800/MF evaporator possessed excellent universal applicability in the treatment process of a complex water system.…”
Section: Resultsmentioning
confidence: 99%
“…As a wide range of refractory organic contaminants was present in the actual water environment, the catalytic efficiency of the CNG-800/MF evaporator was investigated by examining organic pollutants (Figures b, S13). The CNG-800/MF evaporator completely removed SMX within 40 min and RhB and MB within 60 min, and demonstrated removal efficiencies of 90.3% for TC, 95.3% for CBZ, and 83.1% for ATZ within 60 min. These results confirmed that the as-designed CNG-800/MF evaporator possessed excellent universal applicability in the treatment process of a complex water system.…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al [ 137 ] fabricated conjugated microporous polymer sponges by embedding porphyrin/aniline‐based polymers on PU sponges by dip coating technique (as shown in Figure 6b (i–v)) which shows seawater 1.33 kg m −2 h −1 evaporation rate and 87% PTC efficiency. Ivan et al [ 138 ] fabricated a 3D solar evaporator and obtained a 1.4 kg m −2 h −1 evaporation rate and 79% PTC efficiency. The PU sponge acted as a support component to keep the evaporator floating on water and to facilitate faster water conveyance to the top surface of the absorber.…”
Section: Development Of Solar‐driven Interfacial Evaporation Systemsmentioning
confidence: 99%
“…Generally, the naked eyes observe the salt cleaning process in such cases. To enhance the visibility of salt crystals, Ivan et al [ 138 ] dried their solar evaporator using a drying oven after evaporating 10 wt% brine water solution and put it again on the 10 wt% brine water under no light condition. After 5 h, no salt crystal was observed on the evaporator surface as the wastepaper‐derived egg tray‐based solar evaporator dissolved the salt crystals.…”
Section: Development Of Solar‐driven Interfacial Evaporation Systemsmentioning
confidence: 99%
“…35 There are also solar evaporators with mechanisms that induce the diffusion and return of salt ions. 36 However, the specific structure of the hydrogel evaporator makes it difficult to achieve excellent salt resistance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The intermediate water between bound water and free water exists in a delicate interaction state, allowing vaporization with less energy. Liu et al overcame the challenge of balancing heat management and salt resistance by using a three-dimensional hydrogel evaporator with a vertical radiation container . There are also solar evaporators with mechanisms that induce the diffusion and return of salt ions . However, the specific structure of the hydrogel evaporator makes it difficult to achieve excellent salt resistance.…”
Section: Introductionmentioning
confidence: 99%